Diplomacy in Islam: a historical review - Akhmetova, Elmira (Pelanduk Publications Sdn. Bhd., 2017)
This chapter reviews the Islamic concept of diplomacy and its historical applications by exploring some diplomatic mechanisms, which had been widely exploited during the days of the Prophet (SAW), the Abbasid caliphate and the Ottomans.